The Effect of Giving Warm Compresses on Leg Muscle Cramps in Patients Undergoing Hemodialysis at Royal Prima General Hospital - Fika Erfin Rawati Gulo; Selina Br Giawa; Wanda Bagus Pratama; Elis Anggeria (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2024)
Muscle cramps are the most common complication in hemodialysis patients. Muscle cramps often occur in the calves, thighs, fingers, and toes. Warm compresses are a non-pharmacological therapy that is easy to do to help reduce leg muscle cramps. The aimed to determine the effect of giving warm compresses on leg muscle cramps in patients undergoing hemodialysis at the Royal Prima General Hospital. The method uses a quasi-experimental with a one-group pre-test post-test design, using the Wilcoxon test. The results before giving the warm compress 74.3% every week, and after giving it the frequency was 100% every week. Before giving the warm compress' the severity of the cramps was 97.1% very painful, after giving the severity was 100% a little painful. Before giving a warm compress, the duration of 97.1% muscle cramps was 1-10 minutes, after being given 100.0% the duration of muscle cramps lasted ≤1 minute. Before giving a warm compress' muscle cramps were 71.4% and after giving 100%. Based on the frequency p-value 0.03, severity p-value 0.00, duration p-value 0.00, and time p-value 0.02. It was concluded that there was a significant difference in leg muscle cramps before and after giving warm compresses to patients undergoing hemodialysis.